Impacts of the Cost of Quality Components on Business Execution and the Strategies to Minimize the Cost of Poor Quality - Shobhendu Prabhakar (International Journal of Engineering and Management Research, 2019)
his research paper discusses and analyzes the components of the cost of quality (namely the cost of good quality and the cost of poor quality), their impacts on business execution and the company’s bottom line (i.e. profits) and suggests strategies to minimize the cost of poor quality.